2016
DOI: 10.3389/fncel.2016.00280
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis-Promoting Natural Product α-Asarone Modulates Morphological Dynamics of Activated Microglia

Abstract: α-Asarone is an active constituent of Acori Tatarinowii, one of the widely used traditional Chinese Medicine to treat cognitive defect, and recently is shown to promote neurogenesis. Here, we demonstrated that low level (3 μM) of α-asarone attenuated LPS-induced BV2 cell bipolar elongated morphological change, with no significant effect on the LPS-induced pro-inflammatory cytokine expressions. In addition, time-lapse analysis also revealed that α-asarone modulated LPS-induced BV2 morphological dynamics. Consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…erefore, ATEO presents various neurological activities on central nervous system in physiological and pathological conditions. ese activities of ATEO may be relevant to the traditional use of ATR: regaining consciousness, tranquilizing the mind, eliminating dampness, and invigorating the circulation of blood [48].…”
Section: Discussionmentioning
confidence: 99%
“…erefore, ATEO presents various neurological activities on central nervous system in physiological and pathological conditions. ese activities of ATEO may be relevant to the traditional use of ATR: regaining consciousness, tranquilizing the mind, eliminating dampness, and invigorating the circulation of blood [48].…”
Section: Discussionmentioning
confidence: 99%
“…BV2 cell line was originally generated from primary microglial cell cultures (Blasi et al 1990) and has been used frequently as a substitute for primary microglia (Henn et al 2009). A wealth of evidence has revealed that BV2 cells exhibit many similarities with primary microglia (Cai et al 2016; Crotti et al 2014; Das et al 2016; Henn et al 2009; Kim et al 2003). Therefore, the study presented here suggests that human or rat microglia may have some similarity cell responses to HIV-gp120.…”
Section: Discussionmentioning
confidence: 99%
“…5b). A bipolar cell has a lower Feret ratio than a round cell, and thus, this method can be used to assess the level of polarization (bipolarity) in cells 46 .…”
Section: Rad618 Induces Morphological Changes In Oecsmentioning
confidence: 99%